Upaya Penanganan Kenakalan Remaja Melalui Sosialisasi Di SMPN 04 Kampung Jati Mulya - Siswanto Siswanto; Anggi Saraswati; Artha Maria; Christin Sari; Claudia Agustina; Domia Cindirella; Elfander Sinaga; Enny Herawaty; Halashon Binsar; Yoan Sonanta; Yosafat Rumahorbo (Universitas 17 Agustus 1945 Semarang, 2023)
KKN are activities that must be carried out by Riau University students to serve themselves to the community. This research aims to document and analyze efforts to suppress juvenile delinquency through socialization at SMP Negeri 04 Kampung Jati Mulya. Juvenile delinquency is a social problem that requires serious attention from various parties, especially in the educational environment. This research involves analysis of socialization activities carried out by UNRI KKN to shape positive behavior in teenagers and prevent juvenile delinquency. The method used is the observation and socialization stages. As a result of this research, the teenagers of SMPN 04 Jati Mulya are aware that the actions they take will become the basis for their next actions.